2017
DOI: 10.3343/alm.2017.37.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Urine Albumin-to-Creatinine Ratio (ACR) Between ACR Strip Test and Quantitative Test in Prediabetes and Diabetes

Abstract: BackgroundAlbuminuria is generally known as a sensitive marker of renal and cardiovascular dysfunction. It can be used to help predict the occurrence of nephropathy and cardiovascular disorders in diabetes. Individuals with prediabetes have a tendency to develop macrovascular and microvascular pathology, resulting in an increased risk of retinopathy, cardiovascular diseases, and chronic renal diseases. We evaluated the clinical value of a strip test for measuring the urinary albumin-to-creatinine ratio (ACR) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…However, there were several studies to evaluate the diagnostic performance of spot urine for the detection of MAU, since 24-hour urine collection is time and cost consuming. They showed that spot urine was a reliable measure of proteinuria in various subjects with diabetes, prediabetes, chronic kidney disease and rheumatic disease as well as in general population 25 31 . Third, MAU could transiently develop in the presence of inflammation or stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were several studies to evaluate the diagnostic performance of spot urine for the detection of MAU, since 24-hour urine collection is time and cost consuming. They showed that spot urine was a reliable measure of proteinuria in various subjects with diabetes, prediabetes, chronic kidney disease and rheumatic disease as well as in general population 25 31 . Third, MAU could transiently develop in the presence of inflammation or stress.…”
Section: Discussionmentioning
confidence: 99%
“…while those with values of <30 mg/g were considered "negative (12). Reference range of serum creatinine used in this study was (0.6-1.2 mg/dl), serum magnesium (1.6-2.6 mg/dl).…”
Section: Reference Values Of Measured Investigationmentioning
confidence: 99%
“…It is estimated that approximately one-third of the general population is affected by prediabetes ( 2 ). Prediabetes is associated with cardiovascular events ( 3 ) and complications such as nephropathy, ( 4 ) retinopathy, ( 5 ) and neuropathy ( 6 ). In addition, there is an increased risk of conversion to diabetes ( 7 ).…”
Section: Introductionmentioning
confidence: 99%